Optimization of gold nanoparticles electrodeposition duration on screen printed electrode to enhance electrochemiluminescence of nitrogen-doped carbon dots - Mohd Azman, Nurul Izzati Akmal; Ismail, Nur Syakimah; Abdul Halim, Nur Hamidah; Juhari, Nurjuliana; Abd Rahim, Toibah; Sabani, Norhayati; Shamsudin, Siti Aisyah; Tamiya, Eiichi (Universiti Malaysia Perlis, 2023)
In this work, the electrodeposition method was utilized to form gold nanoparticles on a carbon screen-printed electrode (SPE) using chronoamperometry at -0.4 V with various durations from 50 to 200 seconds. Scanning Electron Microscopy (SEM) images have proven that the electrodeposition method is capable of uniformly forming AuNPs on SPE (AuNPsSPE). Apart from that, electrodeposition durations have increased the size of AuNPs by up to 66% based on average size measurements using ImageJ software. It can be observed that long electrodeposition durations permit the agglomeration of AuNPs on the electrode surface. The effect of electrodeposition duration on electrocatalytic performance in potassium ferricyanide and electrochemiluminescence (ECL) intensity of nitrogen-doped carbon dots (NCDs) was evaluated. Cyclic voltammetry (CV) of ferricyanide demonstrates that as the electrodeposition duration increases, AuNPs-SPE shows better electrochemical performance than bare SPE. ECL of NCDs displays that 100 s electrodeposition durations give the highest ECL intensity of 184% compared to bare SPE and have been chosen as the optimum parameter. The ECL mechanisms of bare SPE and AuNPs-SPE reveal that AuNPsSPE has greater electrochemical and ECL performance than bare SPE, as evidenced by the CV of AuNPs-SPE having a faster reduction current, which rises to 87.2% ECL intensity and 510 mV faster ECL occurrence. These phenomena confirmed that the electrodeposition of AuNPs has improved the conductivity of SPE.